18s rDNA Sequence Analysis of Microfungi from Biofloc-based System in Pacific Whiteleg Shrimp, Litopenaeus vannamei Culture - Kasan, Nor Azman; Ghazali, Nurarina Ayuni; Hashim, Nurul Fakriah Che; Jauhari, Iswadi; Jusoh, Ahmad; Ikhwanuddi, Mhd (Asian Network for Scientific Information, 2018)
Background and Objective: One of the major problem in Pacific Whiteleg shrimp, Litopenaeus vannamei farming industry is the accumulation of excess toxicant such as ammonia and nitrite. Biofloc technology served as an alternative solution to solve this problem by recycling the water for sustainable aquaculture management due to water scarcity, bio-security and bio-economy. Biological communities within biofloc are mainly composed of micro-organisms which plays an important role in biodegradation of organic material and removal of toxic contaminants. For the purpose of this study, molecular identification of microfungi isolated from biofloc was conducted. Materials and Methods: Isolation of microfungi composition was conducted by culturing the biofloc samples onto Potato Dextrose Agar (PDA) media which further identified molecularly using 18s rDNA sequences analysis. Results: The identified microfungi includes genus from Aspergillus versicolor, A. Niger, A. tamarii, A. flavipes, A. aculeatus, Penicillium citrinum, P. griseofulvum, Trichoderma virens and Pestalotiopsis microspora. The most dominant microfungi were genus Aspergillus sp. followed by the presence of Penicillium sp. Trichoderma sp. and Pestalotiopsis sp. Conclusion: Existence of microfungi species such as Aspergillus sp. and Penicillium sp. in biofloc were perfect candidate in forming biofloc that could reduce water pollution towards a sustainable aquaculture industry.